İroni ve Gerilim: İkinci Dünya Savaşı Yıllarında İstanbul'da ve Ankara'da Savaş Algısı (Irony and Tension: Perception of War in Istanbul and Ankara during the Second World War Years), Sinan Niyazioğlu1 (2016). Issue 1 (1st June 2020) - Barbosa, Helena
Review of: İroni ve Gerilim: İkinci Dünya Savaşı Yıllarında İstanbul'da ve Ankara'da Savaş Algısı (Irony and Tension: Perception of War in Istanbul and Ankara during the Second World War Years), Sinan Niyazioğlu (2016)Ankara, Turkey: Vekam, 312 pp., ISBN 978-6-05938-806-1, p/bk, €8